BUDAYA GOTONG-ROYONG CERMIN PANCASILA DALAM PENANGGULANGAN COVID -19 (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2022)
Gotong-Royong is a manifestation of the values of Pancasila. At the beginning of 2020, the Indonesian people were hit by an outbreak of the Covid-19 Virus. The Impact of the Covid-19 virus is quite large fr the people of Indonesia. Pancasila, which is based on the spririt of gotong-royong, has become the nation’s main capital in dealing with the Covid-19 pandemic. Mutual cooperation is a basic value of Pancasila and has been very clearly illustrated as the basic of a dynamic ideology. The ideological and sociological capital of the Indonesian nation is large to develop social participation as the nation’s energy in dealing with the spread and preventation of the Covid-19 pandemic and its other impacts. The purpose of this study was to analyze mutual cooperation during the Covid-19 pandemic. This study uses a normative juridical research method by reviewing the Regulation of the Minister of Home Affairs Number 42 of 2005 concerning Guidelines for the Implementation of the Month of Mutual Service. The results of the study show that in the era of the Covid-19 pandemic, mutual cooperation is still carried out by the community in various regions of Indonesia. Mutual cooperation in the Covid-19 pandemic belongs to the social sector. Several regions use different terms in gotong-royong activities, including the Jogo Tonggo Task Force, Tangguh Wani Jogo Village and many others. In this case Gotong-royong is still carried out by the community throughout the Indonesia Territory. Keywords : Gotong-royong, Pancasila, Covid-19